2010
DOI: 10.1016/j.jvs.2010.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Function Predicts Survival After Renal Revascularization

Abstract: Background: To define the relationship between left ventricular diastolic function and survival after renal revascularization.Methods: Seventy-six adult patients (49 women, 27 men; mean age: 63 years Ϯ 13 years) with preoperative echocardiography who underwent renal revascularization for atherosclerotic disease were identified. Echocardiograms were performed and interpreted according to American Society of Echocardiography Recommendations for Use of Echocardiography in Clinical Trials. Diastolic function was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Our results extend previous reports of more prevalent LV diastolic dysfunction in patients with RVHT. [13][14][15] However, most previous studies included a smaller number of patients and control subjects with renal dysfunction 14,16 and/or patients with RVHT undergoing renal artery revascularization. 13,23 Our study included a larger number of patients, most of who had SCr levels <2 mg/ dl.…”
Section: Discussionmentioning
confidence: 99%
“…Our results extend previous reports of more prevalent LV diastolic dysfunction in patients with RVHT. [13][14][15] However, most previous studies included a smaller number of patients and control subjects with renal dysfunction 14,16 and/or patients with RVHT undergoing renal artery revascularization. 13,23 Our study included a larger number of patients, most of who had SCr levels <2 mg/ dl.…”
Section: Discussionmentioning
confidence: 99%
“…The association between LV diastolic dysfunction and ARAS -related CKD persisted after adjusting for age, sex, baseline BP levels and kidney function, diabetes mellitus, smoking status, and the use of statins. 2,15 Also, Ghanami et al 22 found that diastolic dysfunction was frequent (61.8%) in the patients with ARAS who underwent revascularization, and was associated with increased mortality during follow -up.…”
Section: Atherosclerotic Renal Artery Stenosis Renal Revascularizatio...mentioning
confidence: 97%